The use and continuance use of social media applications by small and medium enterprises in Kuwait. Issue 6 (2nd September 2019) - Alzougool, Basil
Abstract : Purpose: The purpose of this study is to explore the use and continued intention to use six social media applications (SMAs) (i.e., Facebook, Twitter, YouTube, LinkedIn, Skype and Instagram) by small- and medium-sized enterprises (SMEs) in Kuwait. Design/methodology/approach: A survey of 357 SMEs in Kuwait was conducted to achieve the study objectives. Findings: The study results showed that SMEs mostly used application was Facebook (by more than three quarters of the SMEs), and the least used one was LinkedIn (by around 6 per cent of the SMEs). Also, approximately third of the SMEs used YouTube, Instagram and Twitter. Of those, more than one third used these applications daily. The study also found that both gaining popularity and enjoyment were the main motivations for using all six applications by SMEs. Moreover, the study found that the applications were mostly used for information, communication and marketing. Research limitations/implications: SMEs used and have continued intention to use SMAs for their enjoyment and usefulness, because other SMEs use them and because of their complementarity. In light of the results, several recommendations were suggested to increase the use and continued intention to use SMAs by SMEs in Kuwait. For academics, it may give them an idea of the extent to which SMEs use SMAs in doing work activities, which they can use as a starting point to investigate other factors that might influence the use SMAs by SMEs. Practical implications: For practitioners especially SMEs owners and managers, it may help to encourage them to use the SMAs and to raise their awareness of the benefits of these applications to their work. Social implications: The findings generally suggest that SMEs need ongoing support from the government, industry or any bodies that are interested in the development of SMEs. This support includes providing a more comprehensive view about SMAs such as raising the awareness of SMEs about the potential benefits of some of these applications such as YouTube, Skype and LinkedIn and conducting training courses that help SMEs to set up rules, procedures and strategies on how to use these various applications. Originality/value: SMAs have a number of characteristics that make it a suitable option for doing SMEs' work activities. Therefore, SMAs could provide SMEs with opportunities for interaction and communication with customers and suppliers. Although the literature describes the different aspects of these applications and their potential benefits for people in general and industry in particular, little research has attempted to explore the actual use of these applications especially by SMEs in developing countries in general and in Kuwait in particular.